Giant bilateral adrenal lipoma in a patient with congenital adrenal hyperplasia. (31st March 2021) - Kienitz, Tina; Schwander, Jörg; Bogner, Ulrich; Schwabe, Michael; Steinmüller, Thomas; Quinkler, Marcus
Abstract : Summary: Apart from adrenal myelolipomas, adrenal lipomatous tumors are rare and only seldom described in the literature. We present the case of a 50-year-old man, with a classical form of congenital adrenal hyperplasia (CAH), which was well treated with prednisolone and fludrocortisone. The patient presented with pollakisuria and shortness of breath while bending over. On MRI, fat-equivalent masses were found in the abdomen (14 × 19 × 11 cm on the right side and 10 × 11 × 6 cm on the left side). The right adrenal mass was resected during open laparotomy and the pathohistological examination revealed the diagnosis of an adrenal lipoma. Symptoms were subdued totally postoperatively. This is the first report of a bilateral adrenal lipoma in a patient with CAH that we are aware of. Learning points: Macronodular hyperplasia is common in patients with congenital adrenal hyperplasia (CAH). Solitary adrenal tumors appear in approximately 10% of adult CAH patients and are often benign myelolipomas. The Endocrine Society Clinical Practice Guideline does not recommend routine adrenal imaging in adult CAH patients. Adrenal imaging should be performed in CAH patients with clinical signs for an adrenal or abdominal mass. Adrenal lipoma is rare and histopathological examinations should rule out a differentiated liposarcoma.